1993
DOI: 10.1126/science.260.5107.523
|View full text |Cite
|
Sign up to set email alerts
|

Record Low Global Ozone in 1992

Abstract: The 1992 global average total ozone, measured by the Total Ozone Mapping Spectrometer (TOMS) on the Nimbus-7 satellite, was 2 to 3 percent lower than any earlier year observed by TOMS (1979 to 1991). Ozone amounts were low in a wide range of latitudes in both the Northern and Southern hemispheres, and the largest decreases were in the regions from 10 degrees S to 20 degrees S and 100N to 60 degrees N. Global ozone in 1992 is at least 1.5 percent lower than would be predicted by a statistical model that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
127
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(141 citation statements)
references
References 15 publications
9
127
0
5
Order By: Relevance
“…The Nimbus 7 TOMS provides total ozone measurements on nearly every day from November 1978 until May 1993 (Stolarski et al, 1991;Gleason et al, 1993). The TOMS measurements are used mainly for validation purposes.…”
Section: Ozonesondesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nimbus 7 TOMS provides total ozone measurements on nearly every day from November 1978 until May 1993 (Stolarski et al, 1991;Gleason et al, 1993). The TOMS measurements are used mainly for validation purposes.…”
Section: Ozonesondesmentioning
confidence: 99%
“…Satellite and ground-based measurements have demonstrated that ozone depletion has been occurring for almost two decades on a global scale [Stolarski et al, 1992;Gleason et al, 1993;World Meteorological Organization (WMO), 1994]. Of particular interest are the trends observed in the northern hemisphere midlatitudes which occur over highly populated areas.…”
Section: Introductionmentioning
confidence: 99%
“…Positive anomalies greater than 2 K could still be seen between 30°N and20°S in February 1992 (Kawamata et al, 1992). A significant decrease of NO2 (Perliski and Solomon, 1992;Koike et al, 1993) and 03 (Gleason et al, 1993;Tie et al, 1994) occurred through the heterogeneous chemical reactions on the sulfate aerosol surface (e.g., Brasseur and Granier, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Such loss equates to the removal of 3% of the world's ozone in a period of six weeks, demonstrating just how rapidly the global state of the atmosphere can change (Anderson et al, 1991). The ozone hole of 1992 showed a very dramatic demonstration of the rate of ozone depletion during austral spring, as measured ozone amounts were about 50% of that of 1979 (Gleason et al, 1993).…”
Section: Introductionmentioning
confidence: 90%